Sharing Place, Learning Together: Perspectives and Reflections on an Educational Partnership Formation With a Remote Indigenous Community School - Godinho, Sally Caroline; Woolley, Marilyn; Webb, Jessie; Winkel, Kenneth Daniel (The Australian Journal of Indigenous Education, 2015)
Sustainable partnership formation in a remote Indigenous community involves social, cultural and political considerations. This article reports on the project, ‘Sharing Place, Learning Together: Supporting Sustainable Educational Partnerships to Advance Social Equity’, funded by the Melbourne Social Equity Institute (MSEI) at the University of Melbourne (UoM). The project's aims were to document insights into working with communities and educators in a remote community school in Western Arnhem Land, and to promote and raise Aboriginal students’ aspirations for engagement in further education through knowledge exchanges. Two project deliverables focus this paper: a participatory workshop conducted at UoM by educators and students from the school, and a qualitative research study that investigated the mutual partnership capacity building between the school community and UoM. The workshop provided an environment conducive to the participants sharing their cultural knowledge and perspectives on a two-way Learning on Country program with the wider UoM community. Extensive interview data collected from school and community-based participants identified the enabling and constraining factors impacting the formation of a sustainable partnership. The findings revealed the importance of prioritising relationship-building, the valuing of resource development, and the need for humility and openness to criticism when working with remote communities.